OPTIMIZATION OF PHYSICOCHEMICAL FACTORS FOR MICROALGAL BIOMASS USING INDIGENOUSLY ISOLATED MICROALGAE - Muhammad Imran Najeeb; Aftab Ahmad Anjum; Mansur-ud-Din Ahmad; Azhar Maqbool; Tehreem Ali; Rabia Manzoor (Journal of Animal and Plant Sciences, 2023)
In the current global energy crisis scenario, microalgae are considered an efficient feedstock for the green synthesis of biofuels. Therefore, it is a dire need of time to screen, select and optimizes the growth conditions of indigenous microalgal strains for enhanced biofuel production. This study was designed to optimize the physicochemical conditions required for the growth of indigenous microalgal strains (n=10). All strains were grown in BG-11 media and optimized for different physical requirements, i.e., pH, temperatures, light intensity, NaCl, and chemical requirements, i.e., carbon source (glucose, glycerol, maltose, acetic acid), nitrogen source (urea, ammonium chloride, potassium nitrate, sodium nitrate), Nitrogen levels, phosphorus level, sodium bicarbonate concentration, and CO2. All strains were grown for 10 days, and growth was monitored by measuring optical density at 650 nm. Results revealed that out of 10 strains, the optimum growth of most of the strains was at 35oC (5/10, 50%), pH 7 (8/10, 80%), light intensity of 2000 lux (5/10, 50%), and 1% NaCl (5/10, 50%). Similarly, most of the strains had higher growth in media supplemented with 40 mM of NaNO3 (7/10, 70%), 2 mM phosphorus (5/10, 50%), 1% glycerol (9/10, 90%) in autotrophic conditions, and 1% glucose (5/10, 50%) in mixotrophic conditions. The overall finding of the study revealed that Scenedesmus AIN01 showed significantly higher growth at 35oC, pH 7, 2000 lux light, 1% NaCl, 40 mM NaNO3, 1.5 mM phosphorus, 1% glycerol, and 0.1% bicarbonate as compared to other strains grown at their optimum conditions. It is concluded that the strains in this study, especially Scenedesmus AIN01, may be grown using their optimum physicochemical conditions for enhanced growth for subsequent use in biofuel production.
Keywords: Light intensity; Microalgae; Nitrogen sources; Salinity; Temperature